Integers, fractions, and arithmetic : a guide for teachers - Sally, Judith D., 1937-; Sally, Paul J., Jr., 1933- (Berkeley CA : MSRI, 2012)
This book, which consists of twelve interactive seminars, is a comprehensive and careful study of the fundamental topics of K-8 arithmetic. The guide aims to help teachers understand the mathematical foundations of number theory in order to strengthen and enrich their mathematics classes. Five seminars are dedicated to fractions and decimals because of their importance in the classroom curriculum. The standard topics are covered in detail, but are arranged in an order that is slightly different from the usual one. Multiplication is treated first, and with that in hand, common denominators and equivalent fractions are more readily understood and are available for use when discussing addition. The book is intended for the professional development of teachers. It is appropriate for teacher education programs as well as for enrichment programs such as Mathematical Circles for Teachers. There are numerous activities in each seminar that teachers can bring into their classrooms.
Includes index.
Keywords: Arithmetic -- Study and teaching (Elementary).; Mathematics education -- Educational policy and systems -- Teacher education; Number theory -- Elementary number theory -- Elementary number theory; Number theory -- Instructional exposition (textbooks, tutorial papers, etc.).; Wiskunde